EBSD characterization of an if steel processed by Accumulative Roll Bonding - Cruz Gandarilla, F. (2015)
The objective of this work is to study the texture and microstructure evolution of an IF steel deformed by Accumulative Roll Bonding (ARB) using Electron Backscatter Diffraction. Texture changes occur with increasing number of ARB cycles. For the early cycles, the main components are the α and γ fiber components characteristic of steels. With increasing the number of ARB cycles a tendency towards a random texture is obtained. In the initial state, the mean grain size is 30 μm and after 5 cycles it decreases to 1.2 μm. For the first ARB cycles, the fraction of high angle grain boundary is low but it increases with the number of cycles to about 80% for 5 cycles. The Kernel Average Misorientation (KAM) has no appreciable changes with the number of ARB cycles for all the texture components.